Paths of Economic Growth that are Optimal with Regard only to Final States: A Turnpike Theorem - Radner, Roy (Review of Economic Studies, 1961)
Prices and the Turnpike: III. Paths of Economic Growth that are Optimal with Regard only to Final States: A Turnpike Theorem1 Roy Radner Roy Radner Berkeley, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 2, February 1961, Pages 98–104, https://doi.org/10.2307/2295707 Published: 01 February 1961